2021
DOI: 10.3390/nu13061978
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Portion Control Tools on Portion Size Awareness, Choice and Intake: Systematic Review and Meta-Analysis

Abstract: Portion control utensils and reduced size tableware amongst other tools, have the potential to guide portion size intake but their effectiveness remains controversial. This review evaluated the breadth and effectiveness of existing portion control tools on learning/awareness of appropriate portion sizes (PS), PS choice, and PS consumption. Additional outcomes were energy intake and weight loss. Published records between 2006–2020 (n = 1241) were identified from PubMed and WoS, and 36 publications comparing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 89 publications
(237 reference statements)
1
7
0
Order By: Relevance
“…Evidence reviews have found limited effectiveness for the following strategies: media campaigns to raise awareness and encourage practicing mindful snacking, intuitive eating, or portion balance communications [25,30]; individual behavioral-change strategies, including visual educational resources to nudge people to reduce eating rate and bite size; providing information on product labels; training for portion-control plates and using smaller cooking, serving, and eating utensils; and business strategies to alter products' sensory properties and portion sizes, to improve product labels, and use resealable packages to discourage overconsumption [30,31].…”
Section: Business and Private-sector Initiatives To Promote Healthy P...mentioning
confidence: 99%
“…Evidence reviews have found limited effectiveness for the following strategies: media campaigns to raise awareness and encourage practicing mindful snacking, intuitive eating, or portion balance communications [25,30]; individual behavioral-change strategies, including visual educational resources to nudge people to reduce eating rate and bite size; providing information on product labels; training for portion-control plates and using smaller cooking, serving, and eating utensils; and business strategies to alter products' sensory properties and portion sizes, to improve product labels, and use resealable packages to discourage overconsumption [30,31].…”
Section: Business and Private-sector Initiatives To Promote Healthy P...mentioning
confidence: 99%
“…The changes in weight were likely due to food-related changes (consuming more salad and vegetables and less energy-dense foods) as a result of participation in the intervention. Furthermore, a recent meta-analysis reports portion control tools marginally induced weight loss especially driven by calibrated tableware [38].…”
Section: Discussionmentioning
confidence: 99%
“…We found comparable results to other previously published reviews. For example, a review conducted by Vargaz-Alvarez and colleagues found portion control tools marginally induced weight loss [84]. However, these tools were inclusive of bowls and cutlery in addition to portion control plates.…”
Section: Discussionmentioning
confidence: 99%